Discrimination, violence, and suicide in transgender women in Iran. Issue 7 (15th June 2022) - Nematollahi, Azar; Farnam, Farnaz; Gharibzadeh, Safoora; Khoda-Khah, Parisa
Abstract: Discrimination, violence, and suicidal thoughts are the most common problems of transgender people that should be considered. In this cross-sectional study we investigated the rates of discrimination, violence, and suicidal behaviors in transgender women. The participants were selected through convenient sampling from August 2019 to March 2020 in Iran. Our results indicated that a significant percentage of participants were subjected to discrimination, physical violence, verbal or emotional violence, sexual violence, suicidal thoughts, and suicide attempts. We concluded that legalizing the process of gender reassignment alone is not enough and without adequate family, social, and health support, these individuals are subject to a variety of threats.